PROS AND CONS OF THE POLICY FOR PROVIDING SOCIAL ASSITANCE AHEAD OF THE GENERAL ELECTION - Bakran Suni (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
One of the things that has become a hot and endless topic of discussion is the government's policy of providing assistance ahead of the 2024 election. One party believes that the policy of providing social assistance ahead of the general election is likely to have an electoral impact on one of the presidential and vice presidential candidate pairs. One of the reasons this happened was because President Joko Widodo seemed to be siding with one of the candidate pairs. This can give rise to sentiment among the wider community which can give rise to the perception that the state budget is used for intervention policy programs that benefit one of the candidate pairs. However, providing social assistance to the community can help overcome poverty before 2024. Providing social assistance is a form of support from the government to underprivileged communities in facing the economic shocks currently being faced. This research is qualitative research with a descriptive approach. Researchers use research data in the form of secondary data obtained from a number of credible sources such as scientific articles, books and a number of other sources that are credible and commonly used in research. These data were analyzed using analytical tools with stages of data collection, data selection, data reduction and drawing conclusions.